2018
DOI: 10.1371/journal.pbio.2006613
|View full text |Cite
|
Sign up to set email alerts
|

MEKK3 coordinates with FBW7 to regulate WDR62 stability and neurogenesis

Abstract: Mutations of WD repeat domain 62 (WDR62) lead to autosomal recessive primary microcephaly (MCPH), and down-regulation of WDR62 expression causes the loss of neural progenitor cells (NPCs). However, how WDR62 is regulated and hence controls neurogenesis and brain size remains elusive. Here, we demonstrate that mitogen-activated protein kinase kinase kinase 3 (MEKK3) forms a complex with WDR62 to promote c-Jun N-terminal kinase (JNK) signaling synergistically in the control of neurogenesis. The deletion of Mekk3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 65 publications
3
17
0
Order By: Relevance
“…Moreover, the inheritance of ciliary remnants may specify self-renewal by enhancing ciliogenesis in daughter cells following mitosis [22]. Here we showed that pathological WDR62 missense mutations caused reductions in the pool of proliferating radial glia during early-mid gestation (E12.5), premature differentiation into intermediate progenitors and immature neurons, resulting in microcephaly without overt increases in cell death which is consistent with our previous in utero knockdown studies and following conditional deletion of WDR62 in the brain [10,37]. Neural defects in WDR62 deleted or mutant mice were associated with clear ciliary abnormalities in the VZ/SVZ including increased dissociation of ciliary membranes from centrosomes which is characteristic of precocious differentiation of radial glia [9,22].…”
Section: Discussionsupporting
confidence: 90%
“…Moreover, the inheritance of ciliary remnants may specify self-renewal by enhancing ciliogenesis in daughter cells following mitosis [22]. Here we showed that pathological WDR62 missense mutations caused reductions in the pool of proliferating radial glia during early-mid gestation (E12.5), premature differentiation into intermediate progenitors and immature neurons, resulting in microcephaly without overt increases in cell death which is consistent with our previous in utero knockdown studies and following conditional deletion of WDR62 in the brain [10,37]. Neural defects in WDR62 deleted or mutant mice were associated with clear ciliary abnormalities in the VZ/SVZ including increased dissociation of ciliary membranes from centrosomes which is characteristic of precocious differentiation of radial glia [9,22].…”
Section: Discussionsupporting
confidence: 90%
“…Moreover, the inheritance of ciliary remnants may specify selfrenewal by enhancing ciliogenesis in daughter cells following mitosis (Paridaen et al, 2013). Here we showed that pathological WDR62 missense mutations caused reductions in the pool of proliferating radial glia during early-mid gestation (E12.5), premature differentiation into intermediate progenitors and immature neurons, resulting in microcephaly without overt increases in cell death which is consistent with our previous in utero knockdown studies and following conditional deletion of WDR62 in the brain (Xu et al, 2018;Xu et al, 2014). Neural defects in WDR62 deleted or mutant mice were associated with clear ciliary abnormalities in the VZ/SVZ including increased dissociation of ciliary membranes from centrosomes which is characteristic of precocious differentiation of radial glia (Jayaraman et al, 2016;Paridaen et al, 2013).…”
Section: Discussionsupporting
confidence: 91%
“…Mitotic spindle orientation [43] Cell cycle (gastric cancer, GC) [44] Regulating intermediate neural and glial progenitors [45] Centrosome amplification (ovarian cancer, OC) [46] Cell cycle, centriole biogenesis, and mitotic spindle orientation [17] Cell growth (lung adenocarcinoma) [34] Regulating neural stem cell division [47,48]…”
Section: Mcph1 (Brit1)mentioning
confidence: 99%
“…The Chk1-Cdc25-Cdk1 pathway is disrupted in Mcph1-deficient mice, which further distorts mitotic spindle alignment and shifts the division plane of neuroprogenitors [16]. Studies on Mcph2 deficiency mice have indicated that MCPH2 mainly functions in neuron proliferation and differentiation by regulating neural stem cell division in the central nervous system [17,18,47,48]. The total number of cells and the thickness of the cortical plate were significantly decreased in Mcph5 KO mice compared with wild-type mice.…”
Section: Mcph Gene Regulate Neurogenesis and Carcinogenesis Through Rmentioning
confidence: 99%